2019
DOI: 10.1186/s12877-019-1171-6
|View full text |Cite
|
Sign up to set email alerts
|

“We live as good a life as we can, in the situation we’re in” – the significance of the home as perceived by persons with dementia

Abstract: Background The coming years will see more persons with dementia living longer at home. However, “the home” is a complex concept with a multitude of meanings, varying among individuals and raising ethical and practical dilemmas in the support provided for this group. This study aims to increase the understanding of experiences and attitudes among persons with dementia related to living at home. Methods Qualitative interviews were conducted with 12 persons, 69 to 89 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 19 publications
1
14
1
Order By: Relevance
“…Despite past studies finding death at home being the primary preference [ 26 – 28 ] and policy goals to enable home deaths, we found that there has not been a change in home deaths over time. Kjellstadli et al [ 29 ] found in a population-based, longitudinal analyses, that general practitioner (GP) home visit(s) and interdisciplinary collaboration(s) in the last 3 months before death, significantly increased the odds of dying at home in a dose-dependent manner.…”
Section: Discussioncontrasting
confidence: 97%
“…Despite past studies finding death at home being the primary preference [ 26 – 28 ] and policy goals to enable home deaths, we found that there has not been a change in home deaths over time. Kjellstadli et al [ 29 ] found in a population-based, longitudinal analyses, that general practitioner (GP) home visit(s) and interdisciplinary collaboration(s) in the last 3 months before death, significantly increased the odds of dying at home in a dose-dependent manner.…”
Section: Discussioncontrasting
confidence: 97%
“…The remark about finding an answer to the question ‘What’s important to you’ in the persons’ narratives illustrate the importance of finding room for such conversations between coordinator and person with dementia. An open approach in these conversations may further help the coordinator gain insight in the persons’ rhythms of daily life at home [ 33 ]. However, we found that it proved challenging for the coordinators to pursue this objective throughout the intervention period.…”
Section: Discussionmentioning
confidence: 99%
“…Within the included studies, there was a belief that changing the physical home environment would make no difference (review question 3). This finding is in sharp contrast to the wider literature which establishes a relationship between the environment and wellbeing for people with dementia living at home (Forsund et al, 2018;Gitlin and Hodgson, 2018;Bartlett and Brannelly, 2019). Whilst the likelihood of being disabled and/or experiencing multiple chronic and complex health conditions increases with age (Office for National Statistics, 2018 cited in Age UK, 2019), appropriate housing (including adaptations) can support older people to stay healthy and live independently for longer (Adams and Hodges, 2018).…”
Section: Discussionmentioning
confidence: 81%
“…The scoping review (review question 3) also found that carers were reluctant to make changes if these would cause confusion or irritation in the person with dementia. In the generic literature, Faeø et al (2019: 3) refer to 'the disturbed rhythms in life at home' because often problem behaviours identified at one point in time may not be the most distressing a few weeks later (see also Gitlin et al, 2010). Within the included studies, there was a belief that changing the physical home environment would make no difference (review question 3).…”
Section: Discussionmentioning
confidence: 99%